Global public health policies : case studies from India on planning and implementation - Ramani, K. V. (Economics collection., 2015)
As per the World Health Organization (WHO), public health refers to all organized measures (whether public or private) to prevent diseases, promote health, and prolong life among the population as a whole. Unfortunately, public health continues to remain neglected in many developing countries due to poor management capacity for effective and efficient delivery of public health services. This book starts with an overall view of public health issues at the global, national and sub-national levels. Challenges faced in the management of global public health programs are illustrated through mini-case studies on Adolescent health, HIV/AIDS, Diarrhoea control, and TB control programs. Live case studies from India towards achieving Millennium Development Goals (MDGs) on maternal health, child health, urban health, and polio eradication highlight the managerial challenges on planning and implementing global public health policies in developing countries. Evidence-based strategic planning, micro-level operational planning, closely monitored implementation, and a well-designed surveillance system are critical for the success of global public health policies in developing countries.